Unraveling the molecular interactions involved in phase separation of glucocorticoid receptor - Stortz, Martin Dario (2020)
Background: Functional compartmentalization has emerged as an important factor modulating the kinetics and specificity of biochemical reactions in the nucleus, including those involved in transcriptional regulation. The glucocorticoid receptor (GR) is a ligand-activated transcription factor that translocates to the nucleus upon hormone stimulation and distributes between the nucleoplasm and membraneless compartments named nuclear foci. While a liquid-liquid phase separation process has been recently proposed to drive the formation of many nuclear compartments, the mechanisms governing the heterogeneous organization of GR in the nucleus and the functional relevance of foci formation remain elusive. Results: We dissected some of the molecular interactions involved in the formation of GR condensates and analyzed the GR structural determinants relevant to this process. We show that GR foci present properties consistent with those expected for biomolecular condensates formed by a liquid-liquid phase separation process in living human cells. Their formation requires an initial interaction of GR with certain chromatin regions at specific locations within the nucleus. Surprisingly, the intrinsically disordered region of GR is not essential for condensate formation, in contrast to many nuclear proteins that require disordered regions to phase separate, while the ligandbinding domain seems essential for that process. We finally show that GR condensates include Mediator, a protein complex involved in transcription regulation. Conclusions: We show that GR foci have properties of liquid condensates and propose that active GR molecules interact with chromatin and recruit multivalent cofactors whose interactions with additional molecules lead to the formation of a focus. The biological relevance of the interactions occurring in GR condensates supports their involvement in transcription regulation.